1989
DOI: 10.1161/01.cir.80.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of prolonged length of hospital stay after coronary bypass surgery.

Abstract: The length of hospital stay after coronary surgery was studied in 4,683 patients undergoing cardiac catheterization followed by coronary Unusually prolonged stay appears to depend on the occurrence of relatively uncommon but severe complications. (Circulation 1989;80:276-284) In recent years there has been considerable interest in controlling hospital costs. This is especially germane with regard to coronary bypass surgery"2 because this operation is the most commonly performed major operation in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
39
1
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 14 publications
9
39
1
6
Order By: Relevance
“…Thus, the combination of diabetes with some of these variables can justify its expression as a risk factor. Our observations related to diabetes were similar to other studies that have shown a higher proportion of diabetics in the group with prolonged hospitalization [9,16,18,21], and that this disorder, itself, is a risk factor for prolonged hospitalization [11,13]. However, other studies found no association between diabetes and risk for prolonged hospitalization [6,7,16].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the combination of diabetes with some of these variables can justify its expression as a risk factor. Our observations related to diabetes were similar to other studies that have shown a higher proportion of diabetics in the group with prolonged hospitalization [9,16,18,21], and that this disorder, itself, is a risk factor for prolonged hospitalization [11,13]. However, other studies found no association between diabetes and risk for prolonged hospitalization [6,7,16].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatsupporting
confidence: 91%
“…About cutoff for prolonged hospitalization, established by the 70 th percentile of the sample, similar to other studies [8,14,16], we should consider that some authors justify a clinical arbitrary choice [10,17]. Bucerius et al [11] justified that these times of hospitalization included almost all patients with postoperative complications able to prolong the intensive treatment.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Study on revision spinal surgeries (9) documented that more levels fused, female gender, unemployment and history of diabetes mellitus would increase hospital LOS. Similar reports in other kinds of surgeries demonstrated that increasing age, female gender, low socioeconomic status and much more comorbidities could increase the duration of hospital stay (16)(17)(18)(19)(20). Linear regression analysis results showed that age > 50 years, volume of intraoperative blood loss (especially more than 500 mL), operation length (particularly more than 180 minutes), increased levels of fused (mainly more than three levels) and the number of comorbid conditions could predict increased hospital LOS.…”
Section: Discussionsupporting
confidence: 54%
“…The origins of this problem are multifactorial and include ischemia-reperfusion injury (IRI). [1][2][3][4][5][6][7] Interest has focused on the potential of anesthetics to protect the heart and lung against IRI, due to their ability to modify oxidant mediated cell injury, s,9 Recently, the intravenous anesthetic, 2,6-diisopropylphenol, propofol, has been shown to have antioxidant properties, l~ Experimental evidence suggests propofol may protect the myocardium and lung against peroxide and peroxynitrite) 2,1s However, a recent study did not provide clinical evidence of protection with propofol anesthesia used for cardiac procedures. I4 The dose of propofol administered (50 to 100 lag.kg-l.min -1) was limited by the concern that propofol may produce hypotension secondary to cardiac depression and vasodilatation.…”
mentioning
confidence: 99%